Mean platelet volume (MPV) as a diagnostic marker in neonatal sepsis - ., Prathyusha; N., Shreekrishna G.; Bhat, Sinchana; P., Sahana (International Journal of Contemporary Pediatrics, 2019)
Background: Neonatal sepsis is a frequent and important cause of morbidity and mortality which accounts for one quarter of neonatal deaths. There are very few studies done in India to evaluate the role of MPV as diagnostic marker of neonatal sepsis. Methods: Prospective case control study in a tertiary care hospital. Neonates > 30 weeks gestation admitted to neonatal intensive care unit during the study period of 1 year with clinically suspected were included in the study. Neonates with Septic screen positive and culture positive sepsis were included in group A and normal neonates were included in Group B. MPV was done for all the subjects and values more than 10.2fl was considered positive. Newborns with congenital anomalies and who were already on antibiotics prior to admission were excluded from the study. Statistical analysis was done using Statistical Package of Social Sciences (SPSS) version 17.0. Results: 106 neonates were included in the study. MPV showed statistically significant difference between the study groups (mean 12.8±1.52, 10.82±1.20 respectively) at a cut of value of 10.2fl and a sensitivity of 93%, specificity of 84 % with a positive predictive value of 83% and negative predictive value of 94%. Conclusions: MPV can be used as an adjuvant marker along with established septic screen to ensure early diagnosis and treatment of neonatal sepsis with no additional expense.